2007
DOI: 10.1353/wp.2008.0001
|View full text |Cite
|
Sign up to set email alerts
|

Civil Society and the Legacies of Dictatorship

Abstract: The literature on civil society in postcommunist regimes highlights its weakness as compared with civil society in other democracies. In this article the authors make a general argument on how different patterns of antecedent dictatorship affect the development of civil society across a range of democracies. They examine the slow emergence of two behaviors associated with a robust civil society—participation in organizational life and in protest—and explain variation across countries as a function of regime hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
63
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 108 publications
(65 citation statements)
references
References 31 publications
2
63
0
Order By: Relevance
“…In particular, post-Communist societies are characterized by lower membership in civic organizations. Bernhard and Karakoç (2007) discuss the extent to which this is a general phenomenon characteristic of post-totalitarian societies.…”
Section: Political Repression Political Attitudes and Authoritarimentioning
confidence: 98%
“…In particular, post-Communist societies are characterized by lower membership in civic organizations. Bernhard and Karakoç (2007) discuss the extent to which this is a general phenomenon characteristic of post-totalitarian societies.…”
Section: Political Repression Political Attitudes and Authoritarimentioning
confidence: 98%
“…Many scholars have demonstrated that communist institutional (political and economic) and individual (attitudinal-behavioural) legacies have a long-lasting and continuous effect on former communist societies (Jowitt, 1992;Magner, 2005;Bernhard and Karakoç, 2007;Dimitrova-Grajzl and Simon, 2010;Pop-Eleches and Tucker, 2013). The impact of the former regime's legacy on informal institutions has also been discussed in the literature (Rose, 1995;Gibson, 2001;Howard, 2003;Gel'man, 2004;Grødeland, 2007).…”
Section: Soviet Legacymentioning
confidence: 99%
“…For the large majority of cases civil society and party institutionalization are democratic resource that take shape at the beginning of an episode, partially shaped by their authoritarian legacies (Bernhard & Karakoç 2007;Hicken and Kuhonta 2014;Rueschemeyer, Stephens, & Stephens 1994) and partially shaped by dynamics of their transitions. On average, the relative size of the between democratic episode variance to the within democratic episode variance is on the order of 4.64x larger.…”
Section: " "mentioning
confidence: 99%
“…A great deal of work has been done on the weakness of civil society in the postcommunist region as a potential threat to sustained democracy in the region (Howard, 2003;Bernhard & Karakoç, 2007;Pop-Eleches & Tucker, 2013). 5 However, there is no consensus regarding the salutary effects of civil society on democracy.…”
mentioning
confidence: 99%